Die Anweisung als Grundfigur dreipersonaler Leistungserbringung nach österreichischem, deutschem und schweizerischem Recht - Steininger, Barbara C. (Jan Sramek Verlag, 2021)
This book deals with the legal institution of "Anweisung" (delegatio, assignatio) under Austrian, German and Swiss law, which can be considered a basic construct for performance in three-party relationships. While it has a broad scope of application in practice, there are substantial uncertainties as to its theoretically complex foundations. Against the background of the three jurisdictions mentioned, the present monograph examines the basic structure and core elements of this legal institution, and also deals with its property law implications. On this basis, the book develops a coherent system which will allow for consistent solutions for individual problems.